Intraoperative REBOA: an analysis of the American Association for the Surgery of Trauma AORTA registry. Issue 1 (11th November 2019) - Vella, Michael A; Dumas, Ryan Peter; DuBose, Joseph; Morrison, Jonathan; Scalea, Thomas; Moore, Laura; Podbielski, Jeanette; Inaba, Kenji; Piccinini, Alice; Kauvar, David S; Baggenstoss, Valorie L; Spalding, Chance; et al.
Abstract : Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a less-invasive technique for aortic occlusion (AO). Commonly performed in the emergency department (ED), the role of intraoperative placement is less defined. We hypothesized that operating room (OR) placement is associated with increased in-hospital mortality. Methods: The American Association for the Surgery of Trauma AORTA registry was used to identify patients undergoing REBOA. Injury characteristics and outcomes data were compared between OR and ED groups. The primary outcome was in-hospital mortality; secondary outcomes included total AO time, transfusion requirements, and acute kidney injury. Results: Location and timing of catheter insertion were available for 305 of 321 (95%) subjects. 58 patients underwent REBOA in the OR (19%). There were no differences with respect to sex, admission lactate, and Injury Severity Score. The OR group was younger (33 years vs. 41 years, p=0.01) and with more penetrating injuries (36% vs. 15%, p<0.001). There were significant differences with respect to admission physiology. Time from admission to AO was longer in the OR group (75 minutes vs. 23 minutes, p<0.001) as was time to definitive hemostasis (116 minutes vs. 79 minutes, p=0.01). Unadjusted mortality was lower in the OR group (36.2% vs. 68.8%, p<0.001). There were no differences in secondary outcomes. After controlling for covariates, there was no association between insertion location and in-hospital mortality (OR 1.8, 95% CI 0.30 to 11.50). Discussion: OR REBOA placement is common and generally employed in patients with more stable admission physiology. OR placement was not associated with increased in-hospital mortality despite longer times to AO and definite hemostasis when compared with catheters placed in the ED. Level of evidence: IV; therapeutic/care management.